Benchmarking higher energy collision dissociation (HCD) by investigation of binding energies of gas‐phase host–guest complexes of hemicryptophane cages. (13th September 2022) - Bayat, Parisa; Gatineau, David; Lesage, Denis; Martinez, Alexandre; Cole, Richard B.
Abstract: Synthesis of host molecules that feature well‐defined characteristics for molecular recognition of guest molecules is often a major aim of synthetic host–guest (H–G) chemistry. A key consideration in evaluating the selectivity of hosts and the affinities of guests is the measurement of binding energies of obtained H–G complexes. In contrast to nuclear magnetic resonance (NMR) or fluorescence measurements that are capable of measuring binding strengths in solution, mass spectrometry offers the opportunity to measure gas‐phase binding energies. Presented in this article is a higher energy collision dissociation (HCD) approach for determining critical energies of dissociation of H–G complexes. Experiments were performed on electrospray ionization (ESI)‐generated H–G pairs in an LTQ‐XL/Orbitrap hybrid instrument. The presented HCD approach requires preliminary calibration of the internal energy distribution of generated ions that was achieved by the use of activation parameters that were known from previous low‐energy collision‐induced dissociation (low‐energy CID) experiments. Internal energy deposition was modeled based on a truncated Maxwell–Boltzmann distribution and characteristic temperature ( T char ). Using this method, critical energies of dissociation were determined for 10 H–G biologically relevant complexes of the heteroditopic hemicryptophane cage host (Host ). Obtained results are compared with those found previously by low‐energy CID. The use of this HCD technique is relatively straightforward, although its implementation does require knowledge (or a presumption) about the Arrhenius pre‐exponential factor of the complexes to obtain their critical energies of dissociation.